LINGUISTIC STUDY OF PHRASEOLOGICAL UNITS AND THEIR CLASSIFICATION (Web of Teachers: Inderscience Research, 2026)
Phraseology is a significant branch of linguistics that studies fixed expressions such as idioms, collocations, proverbs, and other multi-word units. These expressions, commonly referred to as phraseological units (PUs), play a crucial role in enriching language, making it more expressive, figurative, and culturally embedded.